1 - Reconnecting African Sociology to the Mother: Towards a Woman-centred Endogenous Sociology in South Africa - Adesina, Jimi; Magoqwana, Babalwa (African Sociological Review, 2022)
This paper seeks to respond to the call by Castells (2000) for more practical application of Sociology of the 21st Century, taking into consideration the societies it exists in and the contexts in which they are created. Its primary focus is the challenges that face African Sociology in the 21st Century. It builds on Adesina’s (2006a) ‘epistemic interventions’ by centring Isintu (Indigenous languages in South Africa), languages and matriarchal knowledge histories in the African continent. The paper makes use of one of the most enduring African knowledge institution – uMakhulu (the elder mother/grandmother), to argue for the potential reconnections of the African Sociology to its society and the context this institution is embedded in. In pivoting around the elder mother in African Sociology, the paper introduces a “matrifocal’’ sociological understanding of the discipline, shifting the centralising of ‘fathers of the discipline’. The rationale is that in decentralising the hegemonic body of the discipline (‘the father’), the ‘bio-logic’ of the sociological discipline in Africa will be destabilised, thus, developing a sociological narrative that ventures beyond the binaries. The paper explores and integrates the language and values carried by African grandmothers in dealing with socio-political and economic challenges of their societies.